2009
DOI: 10.1002/anie.200804853
|View full text |Cite
|
Sign up to set email alerts
|

A Luminescent Microporous Metal–Organic Framework for the Fast and Reversible Detection of High Explosives

Abstract: Sensors and sensitivity: A highly luminescent microporous metal-organic framework, [Zn(2)(bpdc)(2)(bpee)] (bpdc = 4,4'-biphenyldicarboxylate; bpee = 1,2-bipyridylethene), is capable of very fast and reversible detection of the vapors of the nitroaromatic explosive 2,4-dinitrotoluene and the plastic explosive taggant 2,3-dimethyl-2,3-dinitrobutane, through redox fluorescence quenching with unprecedented sensitivity (see spectra).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
427
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,182 publications
(438 citation statements)
references
References 46 publications
9
427
1
1
Order By: Relevance
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 84%
See 2 more Smart Citations
“…Pioneering work within this field was performed by Li et al who demonstrated the sensitive detection of DMNB and 2,4-DNT in the vapour phase. 37 This work inspired a number of other researchers who subsequently demonstrated the successful detection of explosives, with some selectivity, using zinc, [38][39][40][41][42][43] cadmium, [44][45][46] lithium, 47 indium, 48 europium, [49][50][51][52] and terbium containing metal-organic frameworks. 53 However, the majority of the published research reports the detection of explosives using MOFs through solution-based titrations.…”
Section: −3mentioning
confidence: 84%
“…These results indicate 1' has substantial potential as a sensory material for DMNB. This is of great significance as very few materials have been noted to detect this analyte particularly in the vapour phase, 37 ESI †Section 7 details the previously reported MOFs that have been able to detect this analyte in either vapour or solution phase. Such difficulty in detecting this analyte arises as a result of its unfavourable reduction potential coupled with its aliphatic structure that cannot form π − π interactions with the electron rich frameworks of the MOFs.…”
Section: Fluorescence Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional inorganic materials such as zeolites or mesoporous solids Egeblad et al 2008), MOFs are synthesized under mild conditions, thus allowing systematic design and tuning of their structures and properties at the molecular level (Lin 2005(Lin , 2007Ma et al 2009a). In the past 15 years, MOFs have been molecularly engineered for a variety of applications, such as nonlinear optics (Evans & Lin 2002;Wang et al 2012), separation (Chen et al 2006;Pan et al 2006;Xiang et al 2011;Li et al 2012), gas storage (Rowsell & Yaghi 2005;Dincȃ & Long 2008), chemical sensing (Allendorf et al 2008;Chen et al 2009;Lan et al 2009;Han et al 2010;Xie et al 2010;Kreno et al 2012), biomedical imaging (Rieter et al 2008;deKrafft et al 2009;Lin et al 2009a;Della Rocca et al 2011), drug delivery (Rieter et al 2008;Lin et al 2009a;Horcajada et al 2010;Huxford et al 2010;Taylor-Pashow et al 2010) and heterogeneous catalysis (Seo et al 2000;Kesanli & Lin 2003;Wu et al 2005;Banerjee et al 2009;Wang et al 2009Wang et al , 2011aMa et al 2010a,b;Song et al 2010;Falkowski et al 2011). In particular, with their highly ordered, crystalline structures that can be determined unambiguously by single-crystal X-ray crystallography, MOFs provide an ideal platform to study single-site catalysis with solid materials (broadly defined ...…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Therefore, many efforts have been devoted to the study of fundamental structural aspects to understand and control the several factors that affect the self-assembly of supramolecular architectures. There are several factors affecting the supramolecular assemblies, such as the coordination geometry of metal ions, 17 [44][45][46][47][48] and template effect.…”
Section: Introductionmentioning
confidence: 99%